RELATIONSHIP BETWEEN LOW-COST BOUTIQUE HOTEL’S SERVICASCAPE AND PERCEIVED VALUE, CUSTOMER SATISFACTION EXPERIENCE AND CUSTOMER LOYALTY IN SURABAYA - Marcellia Crenata (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Boutique hotel is small and thematic accommodation, which use servicescapes, uniqueness, personal service, and customer experience as their competitive advantages. Servicescape is term that used to define the landscape where services are experienced, or man-made environment which a service firm delivers services to its customers. It also described as purposeful environment designed to fulfil specific needs of customers. Servicescape categorized as substantive servicescape (SSoS) abd communicative servicescape (CSoS). Substantive servicecsape is servicescape that represents the physical aspects of the environment (atmosphere, facade design, background music, smell, cleanliness, sign, layout, etc.), while communicative servicescape is servicescape that represents the social aspects (cultural elements, behavior of the employee, the way employee communicates with the customers, etc.). In Surabaya, several low-cost boutique hotels tried to grab the opportunity of this phenomenon, by maximized their substantive servicescape and communicative servicescape as their competitive advantage. However, the sustainability of this strategy is still unknown. This research aimed to answer that question by analyze the relationship between low-cost boutique hotel’s servicescape (substantive and communicative) on perceived value, customer satisfaction experience and customer loyalty. The study used multidimensional perceived value and PLS-SEM as analytical tool.